(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2007)
Official and officially recognized inspection and certification system are fundamentally important and very widely used means of food control systems. The confidence of consumers in the safety and quality of their food supply depends in part on their perception as to the effectiveness of these systems as food control measure.
Keywords: Food adulteration and inspection,Food,Food industry and trade,Thực phẩm giả mạo và kiểm tra,Thực phẩm,Công nghiệp thực phẩm và thương mại; Standards,Tiêu chuẩn